2019
DOI: 10.1017/s0956536118000470
|View full text |Cite
|
Sign up to set email alerts
|

Estudio De Conjuntos Departamentales Y Organización De Barrios Utilizando Sensores Remotos Y Geofísica en El Distrito De Tlajinga, Teotihuacan

Abstract: RESUMENEstudios geofísicos, técnicas de sensores remotos y realización de mapas topográficos con GPS diferencial y vehículos aéreos no tripulados (VANT) han proporcionado una mejor comprensión de la organización espacial de los conjuntos departamentales y barrios en Teotihuacán. Nuestras investigaciones demuestran que en contraste con el mapa producido por el Teotihuacan Mapping Project (TMP) (Millon et al. 1973), el distrito de Tlanjinga es más rectangular y está más formalmente organizado, mientras que los c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Unlike in the city center, compounds such as 18:S3E1 and 33:S3W1 (see Blancas et al 2019; Widmer 1987:365) possess irregular forms that likely indicate two things: (1) that there was greater space available to expand residences in the Tlajinga district, and (2) that families added accretionally to their compounds in accordance with the growth of the corporate kin groups that occupied them. This sort of accretional growth and architectural planning is more consistent with a model of self-organization in urban housing—one that was likely constrained by norms or even regulations imposed from city leaders, but was nevertheless not all-controlling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike in the city center, compounds such as 18:S3E1 and 33:S3W1 (see Blancas et al 2019; Widmer 1987:365) possess irregular forms that likely indicate two things: (1) that there was greater space available to expand residences in the Tlajinga district, and (2) that families added accretionally to their compounds in accordance with the growth of the corporate kin groups that occupied them. This sort of accretional growth and architectural planning is more consistent with a model of self-organization in urban housing—one that was likely constrained by norms or even regulations imposed from city leaders, but was nevertheless not all-controlling.…”
Section: Discussionmentioning
confidence: 99%
“…These were more extensive in the second season, when a total of 34 m 2 (49 m 3 ) were excavated primarily in the midpoint of avenue in order to reveal a stratigraphic sequence over two meters deep. It is readily apparent from visual inspection of the topography at the site or in satellite imagery (Blancas et al 2019) that the southern extension of the Street of the Dead running through Tlajinga is lower than the surrounding topography. The extension of the city's central artery into areas 3 km south of the city was first postulated by Paddock (cited in Millon 1973:38), who noted that thin soils on the southern urban fringe may suggest the extension was excavated into tepetate.…”
Section: Excavations Along the Southern Street Of The Deadmentioning
confidence: 99%
“…A similar methodology previously applied in other areas of Teotihuacan, such as Oztoyahualco (Barba y Manzanilla [4]), Teopancazco (Ortiz et al [5]), Tlajinga (Blancas et al [6]), and Techinantitla (Ruvalcaba et al [7]) has demonstrated to be successful in the study of these archaeological contexts.…”
Section: Methodsmentioning
confidence: 99%
“…To the north is a cluster of mounds mapped by the TMP as a triadic group, which could be the primary temple complex for the district; its largest mound is designated 7:S3W1. No controlled excavations have been undertaken in this area, but there is evidence of contemporary exploratory digging, and we previously registered portions of the complex using magnetometry and ground-penetrating radar (Blancas et al 2019).…”
Section: Field Methodsmentioning
confidence: 99%